2019
DOI: 10.1073/pnas.1913324116
|View full text |Cite
|
Sign up to set email alerts
|

The binuclear cluster of [FeFe] hydrogenase is formed with sulfur donated by cysteine of an [Fe(Cys)(CO) 2 (CN)] organometallic precursor

Abstract: The enzyme [FeFe]-hydrogenase (HydA1) contains a unique 6-iron cofactor, the H-cluster, that has unusual ligands to an Fe–Fe binuclear subcluster: CN−, CO, and an azadithiolate (adt) ligand that provides 2 S bridges between the 2 Fe atoms. In cells, the H-cluster is assembled by a collection of 3 maturases: HydE and HydF, whose roles aren’t fully understood, and HydG, which has been shown to construct a [Fe(Cys)(CO)2(CN)] organometallic precursor to the binuclear cluster. Here, we report the in vitro assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 47 publications
4
70
1
Order By: Relevance
“…hydrogenase has an absolute requirement for HydG for activating hydrogenase activity, 36 replacing HydG and its substrate tyrosine with this proposed HydG product 50 carrier results in high activity, quite comparable to that of the conventional maturation using HydE, HydF, and HydG. 40 Moreover, the resulting EPR signals and 13 C ENDOR (when syn-B is synthetically prepared with 13 C-N) are identical to those of the conventionally maturated H-cluster. This semi-synthesis approach is analogous to the prior work assembling the Hcluster with the pre-synthesized binuclear cluster, 34,35 but now rolled back to the mononuclear Fe level.…”
Section: Hydg and The Formation Of An Organometallicmentioning
confidence: 85%
See 2 more Smart Citations
“…hydrogenase has an absolute requirement for HydG for activating hydrogenase activity, 36 replacing HydG and its substrate tyrosine with this proposed HydG product 50 carrier results in high activity, quite comparable to that of the conventional maturation using HydE, HydF, and HydG. 40 Moreover, the resulting EPR signals and 13 C ENDOR (when syn-B is synthetically prepared with 13 C-N) are identical to those of the conventionally maturated H-cluster. This semi-synthesis approach is analogous to the prior work assembling the Hcluster with the pre-synthesized binuclear cluster, 34,35 but now rolled back to the mononuclear Fe level.…”
Section: Hydg and The Formation Of An Organometallicmentioning
confidence: 85%
“…selenocysteine) the cysteine of the synthon was not routinely possible. Here Rao et al 40 show that the cysteine of the synthon is cleaved during the maturation: the sulfur of this cysteine is vectored into the two adt sulfur bridges of the [2Fe] H subunit (as shown by S/Se EXAFS, Fig. 6), while the rest of the cysteine is eliminated (shown by the lack of 13 C and 15 N-pulse EPR signals when using syn-B- 13 C 3 15 Ncysteine and the concomitant appearance of 13 C 3pyruvate in mass spectroscopy).…”
Section: Hydg and The Formation Of An Organometallicmentioning
confidence: 96%
See 1 more Smart Citation
“…[13][14][15][16] More recently, by using a synthetic [(Cys)Fe(CO) 2 (CN)] carrier we have shown that the two sulfur atoms in the adt ligand are derived from the precursor-bound Cys, but that the CH 2 NHCH 2 component is not. 17 Taken together, the biosynthetic origins of the [Fe 2 S 2 (CO) 3 (CN) 2 ] part of the [2Fe] H subcluster are depicted in Scheme 1: all ve diatomic ligands are tailored from tyrosine by HydG; 18 the two sulfur atoms and the two Fe atoms are from the dangler Fe(Cys) site in HydG (which can be reconstituted with Fe 2+ and free Cys in solution 19 ). Remarkably, these components are all delivered to the binuclear cluster assembly in the form of the [(Cys)Fe(CO) 2 (CN)] product of HydG.…”
mentioning
confidence: 99%
“…56,57 More recently, this strategy has been utilized to identify possible intermediates in the assembly of the pre-catalyst. [66][67][68] Arguably, the main impact of artificial maturation to-date has been the simplified preparation of the active enzyme 60,69 including site-selective isotopologues, [70][71][72] which also facilitates rapid screening protocols. 30 Another important aspect is the preparation of [FeFe]-hydrogenases in which the diiron site is synthetically modified in order to generate non-natural H-clusters and enzymes with new properties.…”
Section: Artificial Maturation and Organometallic Variantsmentioning
confidence: 99%